PEMANFAATAN INSTAGRAM SEBAGAI STRATEGI DIGITAL MARKETING RUMAH SAKIT - Kristin, Jeanny; Kevin Gunawan; Lana Asfaradilla; Magdalena Merry Sinaulan; Melvyanti Nur Fauziah; Acep Rohendi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The development of digital technology has driven significant changes in hospital marketing strategies, particularly through the utilization of social media. Instagram, as a visual and interactive platform, has become one of the media widely used by hospitals to build their image, convey service information, and communicate with the public. This study aims to comprehensively analyze the use of Instagram as a digital marketing strategy for hospitals and its impact on branding, user engagement, patient experience, relationship quality, as well as patient interest and visitation decisions. The research method employed is a literature review with a qualitative approach, analyzing national and international journal articles and scientific proceedings published from 2022 to 2025. Data analysis was conducted through thematic synthesis of relevant research findings. The results of the study indicate that consistent and professional use of Instagram positively contributes to increasing brand awareness, building the hospital's image and credibility, strengthening interactivity and engagement, and shaping patient experiences that impact long-term relationship quality. Furthermore, Instagram also influences patient interest and visitation decisions, including within the context of the national health insurance system. However, the effectiveness of this strategy still faces challenges such as human resource limitations, a lack of data analytics-based evaluation, and inconsistency in content management. This study is expected to serve as a reference for hospital management in designing more effective, well-planned, and patient-needs-oriented digital marketing strategies.